Single Axon Branching Analysis in Rat Thalamocortical Projection from the Anteroventral Thalamus to the Granular Retrosplenial Cortex - Odagiri, Saori; Asano, Yoshiya; Meguro, Reiko; Tani, Toshiki; Ichinohe, Noritaka (Frontiers in Neuroanatomy, 2011)
The granular retrosplenial cortex (GRS) in the rat has a distinct microcoluimn-type structure. The apical tufts of dendritic bundles at layer I, which are formed by layer II neurons, co-localize with patches of thalamic terminations from anteroventral thalamic nucleus (AV). To further understand this microcolumn-type structure in the GRS, one of remaining questions is whether this structure extends into other layers, such as layers III/IV. Other than layer I, previous tracer injection study showed that AV thalamic nucleus also projects to layer III/IV in the GRS. In this study, we examined the morphology of branches in the GRS from the AV thalamus in single axon branch resolution in order to determine whether AV axon branches in layer III/IV are branches of axons with extensive branch in layer I, and, if so, whether the extent of these arborizations in layer III/IV vertically matches with that in layer I. For this purpose, we used a small volume injection of biotinylated dextran-amine into the AV thalamus and reconstructing labeled single axon branches in the GRS. We found that the AV axons consisted of heterogeneous branching types. Type 1 had extensive arborization occurring only in layer Ia. Type 2 had additional branches in III/IV. Types 1 and 2 had extensive ramifications in layer Ia, with lateral extensions within the previously reported extensions of tufts from single dendritic bundles (i.e., 30-200 µm; mean 78 µm). In type 2 branches, axon arborizations in layer III/IV were just below to layer Ia ramifications, but much wider (148-533 µm: mean, 341 µm) than that in layer Ia axon branches and dendritic bundles, suggesting that layer-specific information transmission spacing existed even from the same single axons from the AV to the GRS. Thus, microcolumn-type structure in the upper layer of the GRS was not strictly continuous from layer I to layer IV. How each layer and its components interact each other in different spatial scale should be solved future.